The Use of Theoretical Frameworks Guiding Interprofessional Simulation: An Integrative Review. Issue 3 (May 2020) - Bell, Rhonda; Fredland, Nina
Abstract: AIM: The aim of the review was to describe and summarize the use of theoretical premises noted in published studies on the implementation of interprofessional simulation (IPE-Sim). BACKGROUND: IPE-Sim is an educational methodology being used throughout nursing, allied health, and health science programs of study. Understanding frameworks currently used in IPE-Sim is essential in advancing the knowledge of this type of educational methodology. METHOD: An integrative literature review on the use of theories and models guiding IPE-Sim was performed. RESULTS: Ten studies meeting the inclusion criteria were categorized into theoretical frameworks ( n = 4) or competency frameworks ( n = 6) guiding the development and implementation of IPE-Sim and were included in the review. The literature review revealed a lack of consistent theoretical and competency-based frameworks guiding the development, implementation, assessment, and research of IPE-Sim. CONCLUSION: The integrative literature review describes specific theoretical and competency frameworks currently used in the literature on IPE-Sim. Abstract : Supplemental digital content is available in the text.